Outcomes of combination MRI-targeted and transperineal template biopsy in restaging low-risk prostate cancer for active surveillance - Kenneth Chen; Kae Jack Tay; Yan Mee Law; Hakan Aydin; Henry Ho; Christopher Cheng; John Shyi Peng Yuen (Asian Journal of Urology)
Objective: Active surveillance (AS) offers a strategy to reduce overtreatment and now is a widely accepted treatment option for low-risk prostate cancer. An ideal tool for risk-stratification would detect aggressive cancers and exclude such men from taking up AS in the first place. We evaluate if a combination of transperineal template biopsy with magnetic resonance imaging (MRI)-targeted biopsy identifies significant prostate cancer amongst men initially diagnosed with low-risk prostate cancer. Methods: This prospective, single-blinded study included men with low-risk prostate cancer (D'Amico's Criteria) diagnosed on conventional transrectal ultrasound-guided biopsy. Patients first underwent multiparametric MRI of the prostate ≥6 weeks after initial biopsy. Each suspicious lesion is mapped and assigned a Prostate Imaging Reporting and Data System (PIRADS) score. Template biopsy is first performed with the surgeon blinded to MRI findings followed by MRI-targeted biopsy using a robotic transperineal biopsy platform. Results: The age of the 19 men included is 65.4 ± 4.9 years (mean ± SD). Prostate specific antigen (PSA) at diagnosis and at the time of transperineal biopsy were comparable (7.3 ± 1.7 ng/mL and 7.0 ± 1.8 ng/mL, p = 0.67), so were prostate volumes (34.2 ± 8.9 mL and 32.1 ± 13.4 mL, p = 0.28). MRI-targeted biopsy had a higher percentage of cancer detection per core compared to template biopsy (11.7% vs. 6.5%, p = 0.02), this was more than 3 times superior for Gleason 7 disease (5.9% vs. 1.6%, p < 0.01). Four of 18 (22.2%) patients with MRI lesions had significant disease with MRI-targeted biopsy alone. Three of 19 patients (15.8%) had significant disease with template biopsy alone. In combination, both techniques upclassified five patients (26.3%), all of whom underwent radical prostatectomy. Whole mount histology confirmed tumour location and grade. All six patients with PIRADS 5 lesions had cancer detected (66.6% significant disease). Conclusion: A combination of MRI-targeted and template biopsy may optimally risk-classify “low-risk” patients diagnosed on initial conventional transrectal ultrasonography (TRUS) prostate biopsy. Keywords: Active surveillance, Magnetic resonance imaging, Targeted biopsy, Transperineal prostate biopsy, Robotic biopsy, Low-risk prostate cancer